2020
DOI: 10.3390/app10155272
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Width of Corrosion-Induced Cracks in Reinforced Concrete Using a Damage Model Based on Fracture Mechanics

Abstract: Using a finite-element scheme based on a damage model, a numerical system is developed to predict cracks in reinforced concrete beams due to corrosion expansion. The numerical results show that the width of such cracks is affected considerably by (i) the shape of the reinforcing bar, (ii) the presence of stirrups, and (iii) the number of main reinforcement bars. Specimens of reinforced concrete beams are fabricated to simulate those used in the analysis, and we determine how the crack width is related to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Machine learning is a field that has received increased attention from researchers studying steel corrosion in concrete and has been shown to be a promising approach for predicting damage in reinforced concrete structures experiencing corrosion. 51,115,116 Some studies even have used machine learning to predict CT or corrosion initiation in concrete structures. 117,118 However, these machine learning approaches rely on existing collected data on CT that are still subject to the challenges associated with the CT concept and cannot address the big questions that are described in this paper.…”
Section: Improved Approaches To Forecasting Corrosion Of Steel In Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning is a field that has received increased attention from researchers studying steel corrosion in concrete and has been shown to be a promising approach for predicting damage in reinforced concrete structures experiencing corrosion. 51,115,116 Some studies even have used machine learning to predict CT or corrosion initiation in concrete structures. 117,118 However, these machine learning approaches rely on existing collected data on CT that are still subject to the challenges associated with the CT concept and cannot address the big questions that are described in this paper.…”
Section: Improved Approaches To Forecasting Corrosion Of Steel In Con...mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] These reviews clearly indicate that the concept of the so-called "chloride threshold (CT)," also referred to as "critical chloride content," is at the core of a vast number of these investigations, particularly those that focus on modeling chloride transport and chloride binding processes, [25][26][27][28][29][30][31][32][33][34][35] corrosion propagation, 10,18,23,24,[36][37][38][39][40][41] and corrosion-induced damage. [42][43][44][45][46][47][48][49][50][51] Therefore, it is not the objective of this paper to provide another general review on the subject. Instead, this paper critically focuses on the concept of a chloride threshold.…”
Section: Introductionmentioning
confidence: 99%
“…No interface cracks developed at the joint, and the joint interface maintained good continuity before and after the test. Because the width of rust expansion cracks is affected by many factors such as the shape of bar and the presence of stirrups (Okazaki et al, 2020), the width of cracks in the experiments was not measured. However, by observing the cracks of all specimens, it was found that the crack widths of WD specimens (Figure 5A) were relatively larger than those of IC specimens (Figure 5B).…”
Section: Rust Morphologiesmentioning
confidence: 99%
“…This allows an intelligent analysis of the safety performance of structures. Moreover, finite element analysis has been widely used as a better mechanical simulation tool in the structural construction industry [29]. The twin information is divided into two categories based on the analysis of the information that needs to be captured for tension safety assessment: the action to which the structure is subjected and the mechanical properties of the structure.…”
Section: Multidimensional Modeling For Intelligent Discrimination Of mentioning
confidence: 99%